IMPLEMENTASI UPAYA PENANGGULANGAN TINDAK PIDANA CYBER DI ERA TEKNOLOGI - Dwi Putri Melati Januri Hanafiah (Muhammadiyah Law Review Journal, 2022)
Abuse of the internet is also proven by the frequent finding of crimes through the internet network. The existence of social media which also functions as an online buying and selling transaction, but is used by unscrupulous persons to commit crimes, one of the crimes is fraud. Crimes related to the confidentiality, integrity and existence of data and computer systems receive special attention, because these crimes have a different character from conventional crimes. The legal system in Indonesia does not specifically regulate computer crime through the internet. Obstacles found in investigating cybercrime include issues related to legal instruments, the ability of investigators, evidence, and inadequate computer facilities. Efforts that can be made to overcome obstacles found in investigating cybercrime include improving legal instruments, educating investigators, building adequate facilities, increasing investigative efforts and international cooperation, as well as making efforts to combat cybercrime prevention